The place of exercise in the treatment and prevention of muscular-skeletal pain (literature review) - Savytska, Iryna B. (Psychiatry, Neurology and Medical Psychology, 2020)
Topicality. Musculoskeletal pain is the most common complaint from office workers is often associated with repetitive computer work. The topical character of the problem is also due to the high level of disability, behind only respiratory diseases. For the treatment and prevention often recommend physical exercises, but patients Express concerns about physical activity and recommended exercises in the aspect of the fear of strengthening existing pain syndrome. Is of considerable clinical interest the answer to the question: can physical exercise to have an adverse effect on the condition of the patient with chronic pain syndrome. As well as what type of physical exercise the most effective for therapeutic and prophylactic purpose of office workers, mostly working with the computer. Purpose – a literature review on the issue the treatment and prevention of musculoskeletal pain with physical exercise among office workers. Conclusions. Exercise significantly improves physical health parameters, helping to reduce musculoskeletal pain and improve quality of life. Improve the ergonomics of the workplace prevents the development of carpal tunnel syndrome in the dominant hand, but does not affect an existing neck pain, shoulder, lumbar spine, and prevent them. Exercises for relaxation in the workplace reduce the sensitivity pericardialna neck muscles, reduce neck pain, headache. Strength training with weights muscle have high clinical significance and lead to significant prolonged relief of muscular pain in the neck. Total training for fitness (Nordic walking, running, Cycling) showed only a small yet statistically significant acute pain reduction. Exercise General fitness can be recommended for the organization of "life style" and improve employability. Organization of free time of an office worker in physical activity may be one way of reducing the incidence of vertebral pathology office workers. Further study of preventive health the value of physical exercise programs.